Works of R. Edelbauer in Context of Contemporary Austrian Literature of Early 21st Century - E. M. Shastina; Yu. K. Kazakova (Научный диалог)
This study explores the novels of contemporary Austrian writer Raphaela Edelbauer (Raphaela Edelbauer, b. 1990) “The Fluid Land” (Das flüssige Land, 2019), “DAVE” (DAVE, 2021), “The Incommensurables” (Die Inkommensurablen, 2023) in the context of contemporary Austrian literature of the early third millennium. The relevance of the research is driven by the necessity to comprehend the trends in Austrian literature during an era of global changes. It is revealed that, on one hand, the author continues the traditions of Austrian literature of the second half of the 20th century, particularly on a thematic level (Austrian identity, overcoming the past, the false idyll of provincial Austria, conflicts between fathers and children, etc.), while on the other hand, delving into pressing contemporary issues (transhumanism, artificial intelligence, etc.). The concept of fictionality is central to the analysis, exploring the ways and specifics of its implementation in the artistic text in alignment with the author’s communicative intentions. Special attention is given to Edelbauer’s individual style, the uniqueness of narrative organization in the examined genre varieties (parable novel, science fiction novel, historical novel), and the quest for a “personal” language. The novelty of this research lies in the fact that Edelbauer’s work, distinguished by prestigious literary awards in Austria and Germany, has not been a subject of study in Russian literary studies.